Evaluation of sesame crosses for heterosis of yield and yield attributing traits - Jatothu, Jawahar lal; Dangi, Kuldeep Singh; Kumar, S Sudheer (Journal of Tropical Agriculture, 2013)
The extent of standard heterosis of eleven characters of sixty hybrids of sesame developed by crossing 10 lines and 6 testers in line x tester fashion were evaluated during Rabi, 2007-08, 2008-09 at College Farm, College of Agriculture, ANGRAU, Hyderabad, India. The analysis of variance (line x tester) revealed significant differences among genotypes for all the characters studied. The line x tester interactions contributed up to 79.55 per cent for capsule length followed by number of seeds per capsule (77.98%), seed yield per plant (77.15%) and number of effective primaries per plant expressed in per cent (75.75%). The highest percentage of average heterosis was observed for seed yield per plant and number of effective primaries per plant. Five crosses viz., PKDS-62 x IS 562 B , SI7818 x SI-3171, KKS-98049 X SI-3171, KKS-98049 x KMR-78, CST 2001-5 x TKG-22 were identified as potential hybrids with high standard heterosis for seed yield over better yielding commercial hybrid check Swetha til. Testing of these hybrids in all India coordinated trials across different states of the country may result in identification of better hybrids in the near future for commercial exploitation .